Interactions between suicide mortality and unemployment, health and religion in Southeast Asia / Muhammad Shauki Mohammad Raduan - Muhammad Shauki , Mohammad Raduan (2024)
The Covid-19 pandemic has been linked to a rise in suicide mortality, and while many researchers are studying the determinants of suicide, data limitations have hindered progress. This study attempts to provide insights on the determinants of suicide mortality, including the role of religion, using quintile regression. The results reveal several interesting findings that can help policymakers formulate strategies to address this issue. Firstly, there is a positive relationship between urban populations and suicide rates in Southeast Asia. With rising urbanisation in major cities, such as Jakarta, Bangkok, Manila, and Kuala Lumpur in Southeast Asia, plenty of additional problems have to be addressed by the Southeast Asian governments. These problems include housing, congestion, and the escalating cost of living. One solution to this issue is creating employment opportunities in rural areas to minimize migration to urban areas. Secondly, this study found a positive correlation between unemployment and suicide mortality rates, particularly among females. Governmental bodies in Southeast Asian countries need to find immediate solutions to the problem of unemployment as it can minimize the number of unemployed individuals. Unemployment may lead to mental health issues such as depression and eventually suicide ideation. Thirdly, improved access to healthcare facilities is highly beneficial. Mental health professionals are concentrated mainly in urban areas, leading to uneven access to healthcare facilities in the rural parts of Southeast Asia. Governments in Southeast Asia need to ensure even distribution of healthcare professionals, including general healthcare professionals and mental health professionals to enable immediate action during times of crisis. Finally, this study found that a strong religious foundation can help individuals weather challenges. Governments in Southeast Asia should encourage a strong religious foundation to citizens, embedding positive values in their early childhood years. Overall, this study provides policymakers with critical insights into the determinants of suicide mortality, enabling them to formulate strategies to address this important issue.